PERANCANGAN DAN REALISASI MOBIL REMOTE CONTROL MENGGUNAKAN FIREBASE - Dadan Nur Ramadan; Agus Ganda Permana; Hafidudin Hafidudin (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Car Remote Control is a smaller size miniature car, which is controlled directly by the remote or joystick using transmitter module as a communication, in this journal propose design and realization of car remote control based on Internet of things using Firebase Cloud Messaging, first data from joystick application sent to the realtime database, and NodeMCU on car RC synchronizes the data from realtime database . The results obtained average value of delay from realtime database to NodeMCU is 1.191 second, while the value of sending data from the joystick application to Firebase is 3.13 Kb/s for upload and 2.28 Kb/s for download.